FAKTOR PENENTU SIKAP KONSUMEN UNTUK BERBELANJA DARING MELALUI MARKETPLACE - Olivia Barcelona Nasution (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
The purpose of this study is to examine the effect of perceived benefit, perceived website quality and online trust to attitude toward online shopping. This study used a purposive sampling technique that was only consumers who have made purchases online through a marketplace that can be a respondent. The number of respondents who filled out the research questionnaire and which can be processed were 130 respondents. From testing multiple linear regression shows that perceived benefit, perceived website quality and online trust have a significant positive effect on attitude toward online shopping, where attitude is one determinant of person's behavior.